2022
DOI: 10.3390/ijerph191912926
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition-Education-Based Interventions in Gestational Diabetes: A Scoping Review of Clinical Trials

Abstract: Cases of diabetes mellitus have seen a global increase in prevalence, but there are inherent differences in the pathology and management of different types of diabetes. Type 2 and gestational diabetes have the most similar pathophysiology. For that reason, many similar management strategies exist between type 2 and gestational diabetes, including nutrition-based interventions. Diabetes self-management education and medical nutrition therapy have been advanced as cost-effective interventions to manage hyperglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…Moreover, a large amount of literature has confirmed that insulin aspart treatment can greatly reduce nesfatin-1, CTRP12, and blood glucose levels. [31,32] Another study found that the incidence of adverse pregnancy and perinatal outcomes in patients with GDM is greatly reduced by dietary interventions and insulin aspart treatment. [33] The results of this study showed that, after treatment, the proportion of adverse pregnancy outcomes in the observation group was significantly lower than that in the control group, and the proportions of premature infants, macrosomia, fetal distress, neonatal asphyxia, and neonatal hypoglycemia in the observation group were significantly lower than those in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a large amount of literature has confirmed that insulin aspart treatment can greatly reduce nesfatin-1, CTRP12, and blood glucose levels. [31,32] Another study found that the incidence of adverse pregnancy and perinatal outcomes in patients with GDM is greatly reduced by dietary interventions and insulin aspart treatment. [33] The results of this study showed that, after treatment, the proportion of adverse pregnancy outcomes in the observation group was significantly lower than that in the control group, and the proportions of premature infants, macrosomia, fetal distress, neonatal asphyxia, and neonatal hypoglycemia in the observation group were significantly lower than those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a large amount of literature has confirmed that insulin aspart treatment can greatly reduce nesfatin-1, CTRP12, and blood glucose levels. [ 31 , 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…Low‐resource contexts pose a challenge 20 ; for example, the model of care in which women with GDM were followed up throughout their pregnancy by trained healthcare professionals was tested in a low‐resource setting. 72 This model included face‐to‐face counselling with nutritionists and healthcare professionals, whereby women were educated about GDM and its adverse health effects on both mother and baby, were provided with educational booklets, and were motivated to track their dietary pattern and physical activity. The model was found to be effective in reducing the rate of both maternal and neonatal complications in women with GDM to levels similar to women with normoglycemia.…”
Section: Methodsmentioning
confidence: 99%